REDESAIN PASAR ANYAR TANGERANG DENGAN PENEKANAN ARSITEKTUR JAWA BARAT - , HARIST PRATAMA PUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Traditional market generally seen as a dirty area, source of traffic congestion and potential crime. But it turns Traditional Market has a strong capacity if survive the macroeconomic situation is uncertain. The market has been functioning as a savior and provider of employment for some people. It also provides a daily necessity in the number, type and price range to fit the uncertain financial crises of today's society. However management and empowerment of traditional markets is needed, especially in the building of a facility revamping traditional markets. Moreover, many current progress of time the emergence of the modern market are the main competitors for the traditional market. Tangerang city has a traditional market as a capital buffer that has a strategic role in the growth of national and regional economies in the province of Banten. Currently known issues Traditional Market with a negative connotation for some people. One of them like on âPasar Anyar Tangerangâ, which is in desperate need and empowering management with spatial planning and circulation as yet meet the standards of the market. Many problems arise due to be spilled interfere with the accessibility market and cause traffic jams. Therefore, creating a market that facilitate social interaction with the purpose of the flexibility of space in which the course of buying and selling by creating comfort and makes a main attraction though is still unable to compete with other modern markets. Flexibility with characteristic buildings in West Java for the achievement of the market town of character with the local culture will make Newer Markets as a public building for all people.